PENGARUH HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PRODUK GTMAN DI PT. JASA RICKY ABADI - Elvia Putri Faeri Laoli; Kristi Endah Ginting; Eddy Efpraim Barus; Efraim Pengarapenta Sembiring (Lembaga Penelitian dan Pengabdian Kepada Masyarakat-Universitas Darma Agung. (LPPM_UDA), 2020)
This study aimed at determining and analyzing the influence of prices and promotions on the purchase decision of Gtman products at PT. Jasa Ricky Abadi. The phenomena of product prices fixed at PT. Jasa Ricky Abadi were more expensive compared to its competitors and promotions that were less satisfying to consumers. The research method used was quantitative approach. The type of research was quantitative descriptive and the nature of this research is descriptive explanatory. The data collection was done by interviews and questionnaires. The analytical method used was multiple linear regression analysis. The population in this study was consumers who bought products at PT. Jasa Ricky Abadi from January to December 2017. The technique of determining the sample in this study was simple random sampling, so that the sample used amounted to 144 people. The results showed that prices and promotions had significant effect on purchasing decisions at PT. Jasa Ricky Abadi. The results of the analysis of the factors that influenced purchasing decisions showed that between the two variables analyzed, the most dominant influence on purchasing decisions was the price variable. This was proved by the results of the calculation of each variable (t test), where t test was on price variable. The conclusion in this research was that the price variable rejected H0 and accepted H1. Thus partially it showed that price and service quality had positive and significant effect on purchasing decisions at PT. Jasa Ricky Abadi. Simultaneously the price and promotion variables had positive and significant effect on purchasing decisions at PT. Jasa Ricky Abadi.